Epithelioid hemangioma of liver-The first reported case - Adrienn Biro; László Ternyik; Veronika Czoma; Géza Hegedűs; István Bálint; Dezső Tóth; Zsolt Káposztás (Wolters Kluwer Medknow Publications, 2021)
Epithelioid hemangioma, otherwise known as angiolymphoid hyperplasia with eosinophilia, is a rare benign vasoproliferative disease with an unknown etiology. We report the case of a 42-year-old man with routine bloods test showing mildly elevated serum bilirubin level. CT scan revealed a lesion in the left liver lobe not typical of FNH. PET/CT scan and a dynamic liver MRI were consistent with a malignant mass. Surgical resection was performed. Histopathology of the 45 mm mass reported well-defined, slightly lobular proliferations of capillary-sized vessels around several central muscular vessels. Although the endothelial cells revealed a "hobnail" appearance, none of them showed pleomorphism or mitotic activity. Endothelial cells showed reactivity for the endothelial markers (CD34, CD31) and smooth muscle was detected in the blood vessel walls via immunohistochemistry. Despite its benign nature, epithelioid hemangioma of the liver can lead to a diagnostic and therapeutic dilemma due to the malignant looking features on imaging modalities.